Delivering adaptive and context-aware educational scenarios via mobile devices - Gómez, S.; Zervas, P.; Sampson, Demetrios; Fabregat, R. (2012)
Over the past years, there has been several research initiatives in Technology-enhanced Learning (TeL) that investigate the potential of the educational paradigm shift from the traditional one-size-fits-all approach to learning and teaching to adaptive and personalized learning, in which teaching is tailored to individual learners' needs and characteristics (profile) on-demand and in context. On the other hand, widespread ownership of mobile devices and the growth of mobile communications industry have initiated also a growing research trend in TeL, which is commonly referred to as Mobile Learning, where the aspects of adaptivity and personalization can play an important role towards providing learners with adaptive and personalized learning experiences delivered via mobile devices. However, in order to achieve adaptive and personalized mobile learning, tools for processing learners' contextual information and delivering adaptive and context-aware educational scenarios via mobile devices are needed. Thus, in this paper, we aim to address this issue by describing a tool for delivering adaptive and context-aware educational scenarios via mobile devices. © 2012 IEEE.